Estudo do desenvolvimento extra-uterino de Didelphis aurita Wied, 1826, em cativeiro: investigação de critérios para estimativa de idade - Motta, Maria de Fátima Dezonne (1988)
The growth and development of 37 litters of Didelphis aurita were studied in order to establish a method for age estimation. The sample included 11 litters of captive females and 26 litters captured as pouch young in the State of Rio de Janeiro, Brazil, which were subsequently reared in captivity. Serial measurements of body (snout-rump) and tail lenghts and weight, together with sequential observations of development of selected external characters, were made from the first day to one year of age. The life cycle was divided into three periods: pouch life (1-100 days); weaning (100-150 days) and puberty period (150 days on). Nine dental classes were assigned to all spec1mens based on the time of molar erupt1on and replacement of third -premolar. No clear sex differences were observed regarding dental eruption sequences, but in males of Class VI body and tail lengths and weights were significantly greater than in females. Dental eruptlon sequence did not differ between captive and wild caught animals,suggesing tnat env1ronmental conditions had little or no effect on dental development. The study of weight var1ation using individuals of known age, demonstrated that its is not a good age indicator because of high variance. An empirical multiple regression equation was calculated for age estimation using the selected variables. The standard error using random samples was within eight days. Only animals older than 18 days can nave their age assessed by this equation.